Utilization of Indigenous Microorganisms (IMO) on Lactic Acid Content, pH Value, Dry Matter, and Fleigh Value of Anaerobic Fermentation Cassava Skin (Manihot esculenta) - Mulatsih Siswinarti; Pradipta Bayuaji Pramono; Mohamad Haris Septian (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
The purpose of this study was to determine the effect of using Indigenous Microorganisms( IMO) based on soybean cooking water, rice washing water, tofu dregs water, rumen contents liquid, and coconut water as a commercial starter to replace EM4 in the manufacture of fermentation based on the value of lactic acid content, the value of pH, dry matter content, and Fleigh value. This research was conducted at the Laboratory of Animal Husbandry and Fisheries Technology, Faculty of Agriculture, Tidar University. The research method used a completely randomized design with four treatments (P0 = Cassava peel + EM4 (1%) + molasses (3%), (P1 = Cassava peel + IMO 1 (1%) + molasses (3%), (P2 = Cassava peel + IMO 2 (1%) + molasses (3%), (P3 = Cassava peel + IMO 3 (1%) + molasses (3%) and five replications. The data obtained were analyzed using ANOVA and Dunnet's test, using the IBM SPSS 21 tool. The results of this study showed that the use of MOL had a significant effect (P<0.05) on pH but had no significant effect (P>0.05) on lactic acid , dry matter content, and Fleigh value. The conclusion of this study is that the use of MOL can be used as a substitute for a commercial starter because the anaerobic fermentation of cassava peels produced is included in the very good category based on the pH value, lactic acid content, dry matter and the resulting Fleigh value.